A tail of plumage colouration: disentangling geographic, seasonal and dietary effects on plumage colour in a migratory songbird. (12th January 2022) - Mahoney, Sean M.; Reudink, Matthew W.; Contina, Andrea; Roberts, Kelly A.; Schabert, Veronica T.; Gunther, Emily G.; Covino, Kristen M.
Abstract : Plumage ornamentation in birds serves critical inter‐ and intra‐sexual signaling functions. While carotenoid‐based plumage colouration is often viewed as a classic condition‐dependent sexually selected trait, plumage colouration can be influenced by a wide array of both intrinsic and extrinsic factors. Understanding the mechanisms underlying variation in colouration is especially important for species where the signaling function of ornamental traits is complex or when the literature is conflicting. Here, we examined variation in the yellow/orange tail feathers of American redstarts Setophaga ruticilla passing through two migratory stopover sites in eastern North America during both spring and fall migration to assess the role of geographic variation and seasonality in influencing feather colouration. In addition, we investigated whether diet during moult (inferred via stable isotope analysis of feather δ 15 N and δ 13 C) influenced plumage colouration. Our findings indicate that geographic variation, season and diet all influence individual differences in American redstart colouration, represented by both traditional and tetrahedral colour variables. The extent to which these factors influence colour expression however is largely dependent on the colour metric under study, likely because different colour metrics reflect different attributes of the feather (e.g. structural components versus pigment deposition). The effects of diet (δ 15 N) and season were pronounced for brightness, suggesting a strong effect of diet and feather wear/degradation on feather structure. Though hue, a metric that should strongly reflect pigment deposition, also changed from spring to fall, that effect was dependent on age, with only adults experiencing a reduction in ornamentation. Taken together, our results highlight the numerous sources of variation behind plumage coloration and underscores the difficulty of unraveling complex visual signaling systems, such as those in American redstarts.